The Influence of Learnability, Efficiency, Memorability, Errors, and Satisfaction on Consumer Satisfaction Levels in Fintech Fund Applications - Fatikha, Tia Aulia; Wahyudi, Tri Nur (Proceedings International Conference on Education Innovation and Social Science, 2025)
This research aims to analyze the influence of usability dimensions, namely learnability, efficiency, memorability, errors, and satisfaction to the level of consumer satisfaction in using the DANA fintech application. This research is motivated by the importance of user experience (user experience) in increasing loyalty and adoption of fintech services amidst increasingly fierce digital competition. This research is a quantitative study using questionnaires distributed via Google Form as a data collection technique. The population in this study was millennials who actively used the DANA application, and the sample in this study was 130 respondents. The research results show that the satisfaction variable contributes the most and significantly to user satisfaction, followed by errors. Meanwhile, learnability has a significant but negative effect, indicating that complexity in using applications can reduce satisfaction levels. Efficiency and memorability have a relatively smaller influence. Simultaneously, the variables Learnability, Efficiency, Memorability, Errors and Satisfaction influence the variable Consumer Satisfaction Level by 62.8%, then the remaining 37.2% is influenced by variables outside the model.